Implementation of Interpolation on Linear and Quadratic Splines using SciLab - Melda Panjaitan; Siti Nurhabibah Hutagalung (Jurnal Mantik, 2022)
Linear and quadratic spline interpolation to calculate motor vehicle speed data from 0.0-5.0 and measure humidity intensity, looking for missing data due to limited measurements at intervals of 0.5; 5.7; 7,8; 8,10. The use of the scilab programming determines the input variables in translating graphical data. The use of the scilab programming determines the input variables in the translation of graphical data with a linear equation line approach